SAT-LB46 Depression as an Atypical Presentation of Cushing’s Disease - Pahwa, Dhivya (J Endocr Soc, 2020)
Introduction: Cushing’s disease is an abnormal secretion of ACTH from the pituitary that causes an increase in cortisol production from the adrenal glands. Resultant manifestations from this excess in cortisol include multiple metabolic as well as psychiatric disturbances which can lead to significant morbidity and mortality. Case: The patient is a 29 year old woman who presented with fatigue, decreased energy, poor memory and insomnia for 3 months. She noted irregular menses for 4 months. She was referred from her primary doctor for elevated salivary cortisol and DHEA levels. Evaluation revealed BP: 104/76, HR 78, RR 12, BMI 22.7. She was a thin woman without striae, moon face, buffalo hump or bruising. 24 hour urine free cortisol was 90.3 mcg/24hr. One mg dexamethasone suppression test resulted in an AM cortisol of 17.6 ug/dL and ACTH 25 pg/mL. An 8 mg dexamethasone suppression test showed a cortisol level of 1.2 ug/dL with an ACTH <5 pg/mL. The combined results were suggestive of Cushing’s disease. The patient went for MRI of the pituitary which showed a 4 mm hypoenhancing region on the right side of the gland suspicious for a microadenoma. The patient was followed closely and continued to report fatigue and insomnia. Inferior petrosal sinus sampling was performed. Venous blood sampling of ACTH from the periphery at 0 min, 5 min and 15 min were: <5 pg/mL, <5 pg/mL, and <5 pg/mL respectively. On the right at 0 min, 1 min, 5 min, 15 min ACTH levels were: 12 pg/mL, 14 pg/mL, 16 pg/mL, 14 pg/mL. On the left at 5 min and 15 min ACTH measured 8 pg/mL and 7 pg/mL. These findings confirmed the suspicion of a right-sided ACTH-secreting pituitary adenoma. She was referred to a neurosurgeon to evaluate for resection of the adenoma. Due to the ongoing symptoms, the neurosurgical removal of the lesion was expedited and scheduled within several weeks. While awaiting removal the patient sadly took her own life. Conclusion: Aside from the more commonly associated metabolic manifestations of elevated cortisol levels, psychiatric symptoms can be the initial complaint of patients with Cushing’s disease. Symptoms can include fatigue, depressive symptoms, insomnia, and sleep dysregulation. Currently the Endocrine Society Guideline for Cushing’s syndrome does not have any specific recommendations regarding depression screening. Psychiatric complications are a known manifestation of Cushing’s disease. Close follow up and urgent psychiatric referral with the onset of signs of depression or anxiety should be included as part of Cushing’s disease evaluation. Symptoms of mental health disturbances may be subtle and thus all patients with Cushing’s disease should be screened and monitored for underlying psychiatric illnesses. Reference: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5152600/pdf/JMedLife-09-12.pdf